SURGICAL TREATMENT OF CAROTID BODY TUMORS: A SINGLE-CENTER RETROSPECTIVE STUDY - Sladojevic, Milos; Tomic, Ivan; Mutavdzic, Perica; Jovanovic, Ksenija; Roganovic, Andrija; Bisevac-Sladojevic, Jelena; Davidovic, Lazar; Jovanovic, Milan (Medical Research, 2025)
Introduction/Aim: This study presented our experience of surgical treatment of carotid body tumors (CBT).Material and Methods: We retrospectively analyzed patients who underwent carotid surgery between 2009 and 2021. CBT patients were identified, and a control group of patients without CBT was selected using systematic sampling. Demographic and clinical characteristics were compared. Statistical analysis included Student’s t-test, Pearson’s chi-squared test, and Fisher’s exact test.Results: Among 6728 patients operated for carotid pathology, 16 (0.24%) had CBT. Four CBT patients presented with compressive symptoms, while 12 had medium-sized tumors classified as Shamblin I or II. Subadventitial excision was performed in 12 cases; in four, carotid artery resection and reconstruction were necessary. CBT patients were significantly younger than controls (55.8 ± 17.9 vs. 69.2 ± 7.5 years, p = 0.009). The CBT group included fewer males (25% vs. 68.2%, p = 0.001) and fewer smokers (18.7% vs. 50%, p = 0,014). ASA physical status scores were significantly lower in the CBT group (p = 0.001), and hypertension was less prevalent (75% vs. 92.9%, p = 0.03).  Conclusion: Subadventitial resection of CBT with deliberate resection of the external carotid artery is a simple and efficient procedure. A resection of the internal carotid artery during CBT surgery requires immediate repair or replacement. Our findings indicate significant differences in demographic and clinical characteristics between patients with CBT and those undergoing carotid surgery for atherosclerotic disease, emphasizing the importance of careful assessment and individualized management of this specific patient group.
Keywords: Cervical paraganglioma, Carotid Body Tumor, Surgical Treatment.